Advanced oxidation of 4-chlorophenol via combined pulsed light and sulfate radicals methods: Effect of co-existing anions. (1st August 2021) - Hadi, Sousan; Taheri, Ensiyeh; Amin, Mohammad Mehdi; Fatehizadeh, Ali; Aminabhavi, Tejraj M.
Abstract: Pulsed light (PL) technology, which is based on photonic technology involves the application of broadband emission of light with short and high-power pulses is beginning to emerge for the treatment of wastes via advanced oxidation processes (AOP). The present work investigates the efficiency of PL as a light source for persulfate (PS) activation (PL/PS) and 4-chlorophenol)4-CP) degradation, an organic model pollutant. The influencing parameters on 4-CP degradation such as solution pH, reaction time, initial concentration of 4-CP, PS dose, pulse intensity and frequency, and distance from PL source are systematically investigated. With increasing pH from 3 to 9, the 4-CP degradation decreased from 49.79 ± 2.49 to 33.12 ± 1.66%. The 4-CP degradation followed the first order kinetics that was improved with increasing reaction time, PS dose, pulse intensity, frequency of pulse, and decreasing pH, initial 4-CP concentration and distance from the PL source. The presence of sulfate, chloride, and carbonate anions in the solution has the inhibitory effects on 4-CP degradation, while nitrate anion improved the performance of PL/PS system. In addition, presence of humic acid had an inhibitory effect on the PL/PS system, which led to a decrease of reaction rate constant and 4-CP degradation was performed in PL/PS system with OH, SO 4 −, O2 - and 1 O 2 radicals. The contributions of OH and SO 4 − radicals were 46% and 51%, respectively for the 4-CP degradation and synergistic effect of PL/PS system showed a significant influence on 4-CP degradation while using a combination of PL and PS, suggesting that PL is an effective activator of PS. Highlights: The 4-CP degradation by combined pulsed light and sulfate radicals methods was investigated. The contributions of OH and SO 4 − radicals were 46% and 51% for the 4-CP degradation. The presence of SO 4 2−, Cl −, and CO3 2 − anions led to a decrease in reaction rate constant. Graphical abstract: Image 1